Trends in online searching toward suicide pre-, during, and post the first wave of COVID-19 outbreak in China - Chen, Hongguang; Zhang, Konglai; Li, Hui; Li, Mengqian; Li, Shunfei (Frontiers in Psychiatry, 2022)
COVID-19 may increase the risk of suicide, but the conclusion is still unclear. This study was designed to assess the impact of COVID-19 on suicide pre-, during and post-COVID-19 in China. It’s reported that online searching of the public were associated with their offline thoughts and behaviors.This study was designed to explore the online searching towards suicide pre-, during and post-COVID-19 in China.The online search volumes of keywords on suicide, COVID-19, unemployment, and depression were collected in 2019 and 2020, using Baidu Search Index (BSI). A time-series analysis was used to examine the dynamic correlations between BSI-COVID-19 and BSI-suicide. Generalized estimation equation model was used to calculate the coefficients of variables associated with BSI-suicide. The BSI-suicide increased sharply from January 26, 2020 to February 29, 2020, with the year-over-year growth rate soaring from -54% to 5.4%. Joint point regression also showed a significant increase (15.6%). Time-series analysis between BSI-suicide and BSI-COVID-19 showed that the strongest correlation occurred at lag 1+ week and lag 2+ week. In the pre-COVID-19 model, only BSI-depression was associated with BSI-suicide (β=1.38, P=0.008). During the COVID-19 model, BSI-depression (β=1.77, P=0.040) and BSI-COVID-19 (β=0.03, P<0.001) were significantly associated with BSI-suicide. In the post-COVID-19 model, BSI depression (β=1.55, P=0.010) was still significantly associated with BSI-suicide. Meanwhile, BSI-unemployment (β= 1.67, P=0.007) appeared linked to BSI-suicide for the first time.There was a surge in suicide-related online searching during the early stage of the COVID-19 outbreak. One and two weeks after the peak of COVID-19 was the peak of online searching towards suicide. BSI of factors associated with suicide varied at different stages of the COVID-19 pandemic